Chiral Perturbation Strategies for Circularly Polarized Thermally Activated Delayed-Fluorescence Small Molecules: Progress in the Application of Organic Light-Emitting Diodes - Tianwen Fan; Linxian Xu; Hao Tang; Lingyun Wang; Derong Cao (Nanomaterials, 2025)
The application of organic light-emitting diodes (OLEDs) has become widespread, with polarizers commonly employed to mitigate the influence of external light sources on OLED displays. However, when the light signal generated by the OLED emissive layer passes through the polarizer, approximately 50% of the light energy is inevitably lost. Circularly polarized luminescent (CPL) molecules, capable of emitting specific left- or right-handed circularly polarized light, theoretically enable 100% light energy utilization in corresponding OLED devices (CP-OLEDs). With this breakthrough, CPL mechanisms exhibit significant potential for applications in data storage, bioimaging, and 3D displays. In this review, we focus on molecules constructed via a chiral perturbation strategy, analyzing their CPL generation mechanisms and molecular engineering principles. The relationship between these molecular structures and OLED performance is systematically analyzed and summarized. Finally, we critically address current challenges in developing both CPL active materials and devices based on the chiral perturbation strategies, while providing perspectives on future developments and potential challenges in this field.